2001
DOI: 10.1097/00001756-200110080-00035
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin-induced internalization of the ORL1 receptor in human neuroblastoma cells

Abstract: Nociceptin/orphanin FQ (NC) has been proposed as endogenous ligand of the opioid receptor-like 1 (ORL1) receptor. We investigated NC-induced internalization and recycling of the ORL1 receptor in SK-N-BE human neuroblastoma cells. Internalization was proven by receptor binding assay on viable cells. NC promotes a time- and concentration-dependent internalization of the ORL1 receptor (57% of cell surface receptors are lost after 30 min exposure to 1 microM NC) in a clathrin- and ATP- dependent manner. After 30 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…The CCR7 GPCR, like the nociceptin GPCR demonstrates ligand-dependent differences in receptor internalization and desensitization (57)(58)(59)(60). Both GPCRs differentially regulate receptor fate following ligand binding (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCR7 GPCR, like the nociceptin GPCR demonstrates ligand-dependent differences in receptor internalization and desensitization (57)(58)(59)(60). Both GPCRs differentially regulate receptor fate following ligand binding (45).…”
Section: Discussionmentioning
confidence: 99%
“…2), the nociceptin receptor required different ligand-dependent incubation times to mediate receptor internalization. This may reflect the differential functions of the described ligands, since agonists and antagonists were internalized at different rates (57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous groups have investigated the many stages of NOP receptor trafficking (for a thorough review, see Donica et al, 2013). Early work in the NOP receptor field had difficulty in finding agonistinduced internalization (Dautzenberg et al, 2001); however, later reports showed that NOP receptors indeed internalized in response to N/OFQ treatment (Spampinato et al, 2001(Spampinato et al, , 2002. Similar to the kappa opioid receptor disparities in internalization conditions , it is likely that differences reported in the internalization of NOP receptors are due to expression variability and model system used.…”
Section: B Nop Receptors and Kinase Signalingmentioning
confidence: 99%
“…Similar to the kappa opioid receptor disparities in internalization conditions , it is likely that differences reported in the internalization of NOP receptors are due to expression variability and model system used. In most cases, NOP receptors have been shown to start internalizing fairly rapidly, within 5-10 minutes after agonist treatment, with very robust internalization at 1 hour posttreatment in transfected cells (Spampinato et al, 2001;Corbani et al, 2004;Zhang et al, 2012a). As with the mu receptor, the level of internalized receptor depends on the ligand.…”
Section: B Nop Receptors and Kinase Signalingmentioning
confidence: 99%
“…Like all other neuropeptides, the heptadecapeptid N/OFQ is synthesized as a part of a larger precursor named prepro-nociceptin, a 176 aminoacid polypeptide in human, from which N/OFQ and nocistatin are cleaved in brain cells and peripheral neurons [16,17] . Although nociceptin is present in the brain, the liquor and blood, human immune cells and polymorphonuclear cells, the gastrointestinal tract and other organs, there are no data on N/OFQ or its receptor in malignant diseases with exception of human neuroblastoma cell lines [18,19] . This is the first report focusing on nociceptin in hepatocellular carcinoma and other liver diseases.…”
Section: Discussionmentioning
confidence: 99%